Attribution: A New Controversy?. Issue 3 (11th December 2020) - Lim, Ernest
Abstract: Although courts have generally endorsed the contextual, purposive approach to attribution, there remains significant uncertainty in its application. The recent Singapore Court of Appeal's decision in Red Star raised an issue that was hitherto unaddressed by the Singapore and UK courts: whether the claim brought by a solvent company against its fraudulent employee should be barred by the illegality defence where the person who was essentially the sole director and shareholder consented to the employee's fraud. Underlying the simplicity of the facts and issue are difficult questions of law and policy that have important implications for the law of corporate attribution. This article argues that the reasoning and result in Red Star are questionable. In doing so it critically examines the key principles and policies that are at stake and concludes by suggesting a different approach.